Back-shoring or re-shoring: determinants of manufacturing offshoring from emerging to least developing countries (LDCs). Issue 1 (2nd January 2019) - Mohiuddin, Muhammad; Rashid, MD. Mamunur; Al Azad, MD. Samim; Su, Zhan
ABSTRACT: Offshore outsourcing is mainly the flow of tasks from developed to emerging country firms in search of low cost production facilities. Many of these firms are now shifting their outsourcing activities from emerging to least developing countries. This paper shed light on determinants of firms based in emerging countries' decision on shifting their outsourcing to least developing countries and to what extent it differs from developed country firm's offshoring to emerging countries. Survey based data collected from offshoring client firms based first in South Korea and Taiwan and then engaged in re-shoring their outsourcing activities to Bangladesh and data was analyzed by multiple regression analysis. The current study found that offshoring firms enter into re-shoring to least developing countries to avail cost advantages; to have access to supplier capabilities and to focus more on strategic activities as well as to reap advantages from the institutional policy oriented advantages available in least developed countries. The findings revealed that several production factors have effects on firm's re-shoring decision to LDCs. Transferring offshoring to LDCs and exporting from there to the developed country markets, the offshoring creates the global production network (GPN) integrating developing, emerging and developed countries.